Similitudes in the holy qur'an - Rahim, Mohammad Abdul (Islamic Book Service New Delhi, 2008)
Similitudes in the Holy Qur'an examines the parables and metaphors in the Qur'an, illustrating moral and spiritual lessons through vivid comparisons.